2004
DOI: 10.1051/0004-6361:20031603
|View full text |Cite
|
Sign up to set email alerts
|

XMM-Newton observation of the Seyfert 1 ESO 198-G24

Abstract: Abstract. We present the results from an XMM-Newton observation (January 24, 2001) of the bright Seyfert 1 galaxy ESO 198-G24 (z = 0.045). We found that this Seyfert has an intrinsic 2-10 keV luminosity of about 10 44 erg s −1 . This source shows no intrinsic absorption in addition to the Galactic absorption (N H ∼ 3 × 10 20 cm −2 ). We found both with EPIC and RGS that this source possesses significantly steeper spectra below ∼1.5-2 keV than observed at higher X-ray energies, the so-called soft X-ray excess. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…They can be corrected by the addition of a second narrow Gaussian line (at about 99% confidence level), with E = 5.91 Table 2 refer to this fit. The 6.4 keV line is unresolved and has a modest EW, as found by Porquet et al (2004). A previous XMM-Newton observation, performed about two months before, showed a broad and more intense line (Guainazzi 2003), thus suggesting a variation of Object 6.41 ± 0.02 100 ± 19 59…”
Section: Eso198-g024mentioning
confidence: 57%
See 1 more Smart Citation
“…They can be corrected by the addition of a second narrow Gaussian line (at about 99% confidence level), with E = 5.91 Table 2 refer to this fit. The 6.4 keV line is unresolved and has a modest EW, as found by Porquet et al (2004). A previous XMM-Newton observation, performed about two months before, showed a broad and more intense line (Guainazzi 2003), thus suggesting a variation of Object 6.41 ± 0.02 100 ± 19 59…”
Section: Eso198-g024mentioning
confidence: 57%
“…The presence of the second feature is not reported by Porquet et al (2004), but Guainazzi (2003) found a line at 5.70 +0.07 −0.12 keV in the other XMM-Newton observation. We further divided the second XMM-Newton observation in two parts of about 10 ks each.…”
Section: Eso198-g024mentioning
confidence: 68%
“…It is now common knowledge that in most Seyfert AGN, the primary UV to X-ray emission can be attributed to complex interactions between the accretion disc and a corona of relativistic electrons. by Gierliński & Done (2004), Porquet et al (2004), Piconcelli et al (2005) and Miniutti et al (2009) have shown that the soft excess cannot be directly associated to the Wien tail of the the blackbodylike emission from accretion disc observed in the UV, as previously thought (e.g., Singh, Garmire & Nousek 1985;Pounds et al 1986;Walter & Fink 1993), since the thermal continuum requires temperatures far higher than expected. Done et al (2012) suggested that an increase of the disc effective temperature, caused by Comptonization of the 'seed' photons in a cold (kTe < 1 keV) and optically thick plasma (τ 1), may be the reason for the observed excess.…”
Section: Introductionmentioning
confidence: 67%
“…Furthermore, we show that the line originates from a face-on accretion disk, which is consistent with the orientation of the optical BLR (Kollatschny 2003;Liu et al 2017), and it appears to respond to the continuum flux. Notably, relativistic disk lines from H-like O, N, and C were first claimed in the RGS spectra of the Seyfert 1 galaxies, MCG −6-30-15 and Mrk 766 (Branduardi-Raymont et al 2001;Sako et al 2003), as well as in a small number of other AGN, including, for example, NGC 4051 (Ogle et al 2004) and ESO 198−G24 (Porquet et al 2004). The former two cases have since been disputed, with the features possibly arising from a dusty warm absorber (Lee et al 2001;Turner et al 2003), while the broad O profiles in NGC 4051 are consistent with the optical-UV broad line region (Peretz et al 2019).…”
Section: Discussionmentioning
confidence: 94%